SOUTH AFRICA’S POST-APARTHEID FOREIGN POLICY - van Nieuwkerk, Anthoni (My University, 2011)
This study examines foreign policy decision-making processes of the South African government relating to African crises in the period 1994 to 2002. It takes as its point of departure the question of who makes foreign policy, how, and to what effect. The theory relating to foreign policy and public policy gives rise to a variety of models to explain policy formation and in particular decision making in government. From the survey, three models developed by Graham Allison – the rational actor, organisational behaviour, and governmental politics models – are selected to analyse and better understand South African foreign policy decision-making. Foreign policy decision making relating to crises in Nigeria (1995), Lesotho (1998) and Zimbabwe (2000-2002) are examined. The question in each case is which model best helps to enlighten our understanding of the South African foreign policy response to the perceived crisis. Case study materials were gathered by means of primary and secondary literature as well as open, semi-structured interviews with key individuals involved in relevant policy formation processes. Prior to the analysis of decision making the study constructs a view of the institutional settings of post-apartheid foreign policy making, in particular identifying actors and process, and provides a short contextualisation of the crises in Nigeria, Lesotho and Zimbabwe. The study concludes that public policy making ought to be seen as a political problem solving activity in the face of complexity rather than a logical process involving wellinformed calculations by rational actors who seek to maximise economic utility, political power, or organisational effectives. It supports the view that reliance on the dominant rational actor model is inadequate to explain a foreign policy decision or event. Although of limited use it nevertheless acts to clarify issues, such as broad objectives (actions to achieve peace and stability in Africa as well as the promotion of national interests). Little x evidence emerges to suggest that foreign policy decisions can be understood as outputs of large organisations functioning according to regular patterns of behaviour (such as the Presidency or department of foreign affairs). To the contrary, in the years immediately following 1994, senior governmental decision makers were faced with inadequate, inappropriate or malfunctioning organisational settings and procedures, leading to choices being made by a small circle. The governmental politics model assists in identifying, in all three cases, the lack of an ‘action channel’ – that is, a process to allow for the aggregation of competing perceptions and preferences for making decisions and taking action. Whether institutional overhaul (integrated governance, the cluster system, policy frameworks and a National Security Council) improved matters in later years could not be fully determined. The study found that the governmental politics model was difficult to operationalise because certain data relating to decision making processes remain confidential. The study concludes with recommendations regarding the application of Allison’s models in the South African setting
Ph.D thesis - CLM
Keywords: Foreign policy; South Africa